2019
DOI: 10.5757/asct.2019.28.5.142
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of Plasma Enhanced Atomic Layer Deposition of Si3N4

Abstract: Silicon nitride (SiN x) thin films have attracted interest as an important material for use in next-generation devices such as a gate spacer in 3D fin field-effect transistors (finFETs), charge trap layers, etc. Many studies using the SiN x plasma enhanced atomic layer deposition (PEALD) method have been conducted, owing to its advantages over other SiN x deposition methods. In this review, the recent studies on PEALD of SiN x thin films are summarized, and the effects of some process parameters including plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This is the case for planar substrates such as, for example, dense polymer foils, and also specifically for substrates with three-dimensional features such as porous polymers or membranes. [12,62] Like PECVD, PEALD has been successfully commercialized in the field of encapsulation technology, namely for the deposition of gas or water vapor barrier layers required in highly sensitive organic light-emitting diode displays. [63][64][65] Due to the inherently strong contribution of surface chemistry to film growth in PEALD, it was found that not only the adjustment of plasma parameters in the process allowed to fine-tune thin film properties and thus gas and vapor barrier performances, [66][67][68][69] but that the applied precursor chemistry can play a pivotal role as well.…”
Section: Pealdmentioning
confidence: 99%
“…This is the case for planar substrates such as, for example, dense polymer foils, and also specifically for substrates with three-dimensional features such as porous polymers or membranes. [12,62] Like PECVD, PEALD has been successfully commercialized in the field of encapsulation technology, namely for the deposition of gas or water vapor barrier layers required in highly sensitive organic light-emitting diode displays. [63][64][65] Due to the inherently strong contribution of surface chemistry to film growth in PEALD, it was found that not only the adjustment of plasma parameters in the process allowed to fine-tune thin film properties and thus gas and vapor barrier performances, [66][67][68][69] but that the applied precursor chemistry can play a pivotal role as well.…”
Section: Pealdmentioning
confidence: 99%
“…The LPCVD could allow uniform deposition of many thin-film materials on substrates without damaging effects on film homogeneity at higher temperatures, >600 °C. Conversely, PECVD functions at low temperatures (200 to 400 °C) due to thermal cycle concerns or material limitations, but the films grow faster [ 127 ]. In conclusion, a specific deposition process depends on several factors, e.g., source, substrate structure, apparatus, working temperature, deposition rate, and production time.…”
Section: Techniques Of Preparation Of Mns (Mns)mentioning
confidence: 99%
“…112,113 However, the PECVD process does not entirely avoid the drawbacks, such as electrical damage to the device, mechanical deformation of the film, and nonstoichiometric silicon nitride film formation, significantly reducing the product yield. 114–118 To overcome these limitations, An et al suggested two-sequential processes comprising LACVD and laser-assisted plasma-enhanced chemical vapor deposition (LAPECVD) (Fig. 6a).…”
Section: Laser-assisted Chemical Vapor Depositionmentioning
confidence: 99%